2006
DOI: 10.1111/j.1439-0434.2006.01153.x
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Fungal Pathogens Associated with Grapevine Nurseries and the Decline of Young Vines in Spain

Abstract: The occurrence of fungal grapevine trunk pathogens associated with grapevine nurseries and the decline of young vines in Spain was determined in extensive surveys conducted in nurseries and vineyards with young plants. The presence of Phaeomoniella chlamydospora, Phaeoacremonium aleophilum, Cylindrocarpon spp., Botryosphaeria obtusa and Botryosphaeria spp. was detected in all the surveys that were carried out. This study provides evidence for the presence of these pathogens in Spanish grapevine nurseries. Cyli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(51 citation statements)
references
References 15 publications
1
48
0
Order By: Relevance
“…Once the grafting process terminated, nursery plants do contain damaged tissues that can be invaded by these fungal saprobes. In fact, several earlier studies reported Phaeomoniella chlamydospora and Phaeoacremonium species from nursery plants (Chicau et al 2000;Edwards and Pascoe 2004;Giménez-Jaime et al 2006;Halleen et al 2003). However, Halleen et al (2003) observed that these esca-associated fungal species were mostly associated with either the rootstock or the graft union.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Once the grafting process terminated, nursery plants do contain damaged tissues that can be invaded by these fungal saprobes. In fact, several earlier studies reported Phaeomoniella chlamydospora and Phaeoacremonium species from nursery plants (Chicau et al 2000;Edwards and Pascoe 2004;Giménez-Jaime et al 2006;Halleen et al 2003). However, Halleen et al (2003) observed that these esca-associated fungal species were mostly associated with either the rootstock or the graft union.…”
Section: Discussionmentioning
confidence: 82%
“…The assumption of a wood decomposer community that is specific to damaged plant tissues may also explain why we did not find any of the early esca-associated fungi in nursery plants that were grafted with identical rootstock as the adult plants and with healthy scions sampled from the same adult plants studied here. Indeed, the major risk for potential transmission of fungi associated with esca and young vine decline is generally assumed to be during the grafting process of the grapevine cultivar on a new rootstock Giménez-Jaime et al 2006;Aroca et al 2010). However, if pioneer esca species were indeed fungal saprobes specialized in wood decay, grapevine healthy shoots of the rootstock mother plant and of the selected cultivar used for grafting are unlikely to host any of these fungi.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It may also happen because of the use of infected mother plants (10,12). Rootstock material used for propagation has been reported to harbor trunk disease pathogens and especially Phaeoacremonium species (1,11,13,15,30). Phaeomoniella chlamydospora and Phaeoacremonium spp.…”
mentioning
confidence: 99%
“…Neonectria macrodidyma is a pathogen of economic importance to containerized seedlings and the nursery industry in California [5,6]. It is also important in apple [7], pine and other conifer seedlings, and the forest nurseries [8,9].…”
Section: Introductionmentioning
confidence: 99%